The Level of Psychological Energy and Its Relationship to the Performance of Some Basic Skills in Handball among Young Players in Jordan - Sha’lan, Maen Ahmad Mahmoud; Al-Zaghilat, Muhannad Odeh; Al Madanat , Amjad Najeeb (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to determine the level of psychological energy among young handball players and to explore the relationship between psychological energy and the performance of some basic skills. Methods: The study used a descriptive approach، and its population consisted of young handball players in Jordan who participated in the Youth League for the 2022/2023 season and were born in 2004-2005. The study sample comprised 132 players who were randomly selected. The researchers used the Psychological Energy Scale developed by Al-Khaza'i (2004)، which consisted of 37 items. The following classification was used to judge the level of psychological energy: low (1-1.99)، moderate (2-2.99)، and high (3-4). The study also employed tests for passing and receiving against a wall for 30 seconds، shooting accuracy، and a 15-meter agility test. Results: The study found that the level of psychological energy among handball youth in Jordan came to a high degree، and there was an inverse correlation between the level of psychological energy and the time of performing the dribbling skill; as psychological energy levels increased، the time to complete the dribbling skill decreased. Furthermore، there was a positive correlation between psychological energy and the performance level of passing and receiving as well as shooting accuracy; as psychological energy levels increased، the performance level in these skills also improved. Conclusion: The study highlights the necessity of having sports psychologists for each team to monitor and develop psychological aspects alongside skill and physical preparation of players.